Toward Identifying Alternatives to Fencing for Forest Restoration: Tube Shelters Outperform Mesh Shelters for Deer Browse Protection of Live Oak, Quercus virginiana - Emily C. Thyroff; Owen T. Burney; Juan A. Oliet; Caleb H. Redick; Douglass F. Jacobs (Land, 2022)
Herbivory is a common forest regeneration challenge across ecosystems. While fencing effectively reduces animal browse damage, it can be impractical. Tree shelters are an alternative forest restoration tool to protect seedlings from herbivory that may also provide a favorable microclimate. Yet, regeneration responses to tree shelters often vary among tree species, environmental conditions, and shelter specifications. To restore the once dominant Quercus virginiana (live oak) and its associated conservation values to subtropical U.S. maritime forests, control of animal browsing is critical. We evaluated the effects of tube and mesh tree shelters to exclude animal browse, combined with the use of controlled-release fertilizer to promote Q. virginiana seedling growth. After two growing seasons, mean seedling survival was 83% for protected seedlings, either from tube or mesh shelters, compared to 68% with non-sheltered seedlings. Seedlings in solid-wall tube shelters had significantly less browse incidence compared to both seedlings in mesh shelters and non-sheltered seedlings. Seedlings in tube shelters had greater height and diameter, followed by mesh shelters, and lastly, the no shelter treatment. Fertilizer resulted in higher browsing incidence and greater seedling height and diameter after the first growing season only, with no shelter treatment interactions. Our findings illustrate the efficacy of tree shelters to improve early regeneration success of Q. virginiana and may have application to the restoration of other forest ecosystems.